Topotactic fabrication of transition metal dichalcogenide superconducting nanocircuits - Xiaohan Wang; Hao Wang; Liang Ma; Labao Zhang; Zhuolin Yang; Daxing Dong; Xi Chen; Haochen Li; Yanqiu Guan; Biao Zhang; Qi Chen; Lili Shi; et al. (Nature Communications, 2023)
Abstract Superconducting nanocircuits, which are usually fabricated from superconductor films, are the core of superconducting electronic devices. While emerging transition-metal dichalcogenide superconductors (TMDSCs) with exotic properties show promise for exploiting new superconducting mechanisms and applications, their environmental instability leads to a substantial challenge for the nondestructive preparation of TMDSC nanocircuits. Here, we report a universal strategy to fabricate TMDSC nanopatterns via a topotactic conversion method using prepatterned metals as precursors. Typically, robust NbSe2 meandering nanowires can be controllably manufactured on a wafer scale, by which a superconducting nanowire circuit is principally demonstrated toward potential single photon detection. Moreover, versatile superconducting nanocircuits, e.g., periodical circle/triangle hole arrays and spiral nanowires, can be prepared with selected TMD materials (NbS2, TiSe2, or MoTe2). This work provides a generic approach for fabricating nondestructive TMDSC nanocircuits with precise control, which paves the way for the application of TMDSCs in future electronics.